2004
DOI: 10.1074/mcp.m300127-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

The Human Plasma Proteome

Abstract: We have merged four different views of the human plasma proteome, based on different methodologies, into a single nonredundant list of 1175 distinct gene products. The methodologies used were 1) literature search for proteins reported to occur in plasma or serum; 2) multidimensional chromatography of proteins followed by two-dimensional electrophoresis and mass spectroscopy (MS) identification of resolved proteins; 3) tryptic digestion and multidimensional chromatography of peptides followed by MS identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
313
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 834 publications
(326 citation statements)
references
References 24 publications
11
313
0
2
Order By: Relevance
“…A re-evaluation of three published plasma proteomic studies also indicated that there was minimum overlapping of proteins identified from different proteomics platforms. The proteins found through the literature search are strongly biased toward signal sequence-containing extracellular proteins, while the three proteomics methods showed a much higher representation of cellular proteins, including nuclear, cytoplasmic, and kinesin complex proteins [55].…”
Section: Multiplexed Proteomics Platform For Plasma/serum Protein Idementioning
confidence: 99%
“…A re-evaluation of three published plasma proteomic studies also indicated that there was minimum overlapping of proteins identified from different proteomics platforms. The proteins found through the literature search are strongly biased toward signal sequence-containing extracellular proteins, while the three proteomics methods showed a much higher representation of cellular proteins, including nuclear, cytoplasmic, and kinesin complex proteins [55].…”
Section: Multiplexed Proteomics Platform For Plasma/serum Protein Idementioning
confidence: 99%
“…Most of the relevant information is available in three leading articles published in 2004 [25][26][27]. Combination of several approaches, including a literature survey, permitted Anderson et al [25] to build one of the most precise available lists of human plasma proteins. Chan et al [26] analyzed the serum proteome by combining multidimensional peptide separation strategies and MS/MS [26].…”
Section: Descriptive Plasma/serum Proteomicsmentioning
confidence: 99%
“…In this work we have applied the DIGE approach to study the changes in the cellular proteome in response to chronic adaptation to hypertonic stress in IMCD3 cells. As with any current proteomic technique, DIGE allows for the study of changes to only a fractional subset of the proteome (32,33). In our studies, the small, calcium-binding protein S100A4 was determined to be highly up-regulated by DIGE analysis, Western blot, gene chip analysis, and quantitative PCR.…”
Section: Discussionmentioning
confidence: 91%